Genome-wide characterization of the MADS-box gene family in Paeonia ostii and expression analysis of genes related to floral organ development - Xueting Yang; Qi Guo; Shaodan Liu; Duoduo Wang; Dingding Zuo; Tongfei Niu; Dongfeng Wei; Lili Guo; Xiaogai Hou (BMC Genomics)
Abstract Background Paeonia section Moutan DC. is a significant perennial subshrub, the ornamental value of which heavily depends on the type of flower it possesses. MADS-box transcription factors have a particular impact on the intricate process of floral organ development and differentiation. The release of the whole-genome data from Paeonia ostii now allows us to conduct a thorough investigation of the tree peony MADS-box gene family. Results In this study, we identified 110 MADS-box genes in Paeonia ostii that were classified into 5 subgroups. Gene structure, domain and motif analyses revealed the conservation of the structure of these subgroups. Analysis of the cis-acting elements revealed that the 110 PoMADS genes contained different kinds of hormones and stress-related cis-acting elements in their promoter regions. Quantitative real-time PCR analysis was employed to validate the expression patterns of some PoMADS genes related to floral organ development. Genome collinearity analysis with Arabidopsis and grape revealed the conservation of PoMADS genes during evolution. A total of 857 SSRs were identified by analysing the genome sequences of identified genes. We additionally created protein‒protein interaction networks for PoMADS proteins and analysed proteins that could interact among PoMADSs in Arabidopsis thaliana and grape. Conclusion These findings offer fundamental insights for understanding the function of the MADS-box gene family, which can aid in the selection and breeding of tree peony varieties with high ornamental value in addition to supporting the understanding of the process of tree peony floral organogenesis.